2001
DOI: 10.1209/epl/i2001-00357-4
|View full text |Cite
|
Sign up to set email alerts
|

Absolute acoustic band gap in coupled multilayer structures

Abstract: We show theoretically that by combining two or more finite superlattices, it is possible to realize an omnidirectional acoustic mirror that prevents propagation of acoustic waves over a wide range of frequencies. An appropriate choice of the elastic parameters in the superlattices enables us to propose a structure in which any incident wave launched from any type of substrate (or vacuum) falls inside a minigap of the coupled SLs and therefore undergoes a total reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…As mentioned in the case of photonic band gap materials, one solution would be to associate the superlattice with a cladding layer having high velocities of sound in order to create a barrier for the propagation of acoustic waves. Another solution will consist of associating two superlattices chosen appropriately in such a way that the superposition of their band structures displays a complete acoustic band gap [56,57].…”
Section: Case Of Solid-solid-layered Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the case of photonic band gap materials, one solution would be to associate the superlattice with a cladding layer having high velocities of sound in order to create a barrier for the propagation of acoustic waves. Another solution will consist of associating two superlattices chosen appropriately in such a way that the superposition of their band structures displays a complete acoustic band gap [56,57].…”
Section: Case Of Solid-solid-layered Mediamentioning
confidence: 99%
“…Among these applications, one can mention (1) omnidirectional band gaps [55][56][57][58], (2) the possibility to engineer small-size sonic crystals with locally resonant band gaps in the audible frequency range [59], (3) hypersonic crystals [60-63] with high-frequency band gaps to enhance acousto-optical [49][50][51] or optomechanical [64,65] interaction and to realize stimulated emission of acoustic phonons [66], and (4) the possibility to enhance selective transmission through guided modes of a cavity layer inserted in the periodic structure [6,67] or by interface resonance modes induced by the superlattice/substrate interface [68][69][70]. The advantage of 1D systems lies in the fact that their design is more feasible and they require only relatively simple analytical and numerical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The interest is continuously growing for applications in nano wave devices for terahertz acoustic phonons [3][4][5], spatial and spectral technology of acoustic modes in solids [6][7][8][9][10], acousto-optical multiple interference switches [11] and narrow-band detectors [12]. Many of these applications come from the very high level of control and perfection reached in the growth techniques of microstructures and nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor superlattices are very important for applications: they can operate as phonon mirrors, filter and different kinds of devices [8,9]. In particular acoustic cavities formed by introducing a layer of a different material or a layer with a different thickness in a finite superlattice have been demonstrated recently [3,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of the elastic waves in quasiregular systems following different sequences have already been performed [11][12][13][14][15][16][17][18]. Other studies of elastic waves in multilayer systems, including finite periodic superlattices [19,20], have shown the possibility to produce omnidirectional acoustic mirrors. Other studies of elastic waves in multilayer systems with planar defects have shown the filtering possibilities of these systems [21,22].…”
Section: Introductionmentioning
confidence: 99%